Impact of Net Working Capital and Net Sales on Profitability of PT XYZ - Maula Rahmadona; Eka Rahim (Indonesian Development of Economics and Administration Journal, 2025)
This study aims to analyze the effect of net working capital and net sales on net profit at PT Mayora Indah Tbk during the 2014–2024 period. Methodology/approach – This study uses a quantitative method with annual financial report data for eleven years and is analyzed using multiple linear regression, t-test, F-test, and coefficient of determination with the help of SPSS software version 25. Findings – The results of the study show that net working capital has a significant positive effect on net profit, net sales have no significant effect, and simultaneously both have a significant effect with a determination value of 80.8%. Novelty/value – The novelty of this research lies in the long analysis period covering the COVID-19 pandemic and the finding that efficient working capital management plays a greater role in increasing profits than increasing sales.